Protective effect of cinnamon extract against cobalt-induced multiple organ damage in rats - Isik, Bahar; Suleyman, Bahadir; Mammadov, Renad; Bulut, Seval; Yavuzer, Bulent; Altuner, Durdu; Coban, Taha Abdulkadir; Suleyman, Halis (Frontiers in Pharmacology, 2024)
Background The role of oxidative stress and inflammation in cobalt (Co) toxicity has been the focus of previous studies. Cinnamon and its main components have been reported to have protective effects in various tissues with antioxidant and anti-inflammatory effects. Aims In this study, the protective effect of cinnamon extract (CE) against possible Co-induced heart, kidney, and liver damage in rats was investigated biochemically. Methods Eighteen albino Wistar-type male rats were categorized into three groups (n = 6 per group): control (CG), CoCL2-administered (CoCL2), and CE + CoCL2-administered (CE + Co) groups. The CE + CoCL2 group was administered CE (100 mg/kg), and the CoCL2 and CG groups were administered distilled water orally by gavage. One hour after the administration, Co (150 mg/kg) was administered orally to the CE + CoCL2 and CoCL2 groups. This procedure was repeated once daily for 7 days. Then, biochemical markers were studied in the excised heart, kidney, and liver tissues. Results CoCL2 increased oxidants and proinflammatory cytokines and decreased antioxidants in heart, kidney, and liver tissues. Heart, kidney, and liver tissue were affected by Co damage. CE treatment suppressed the CoCL2-induced increase in oxidants and proinflammatory cytokines and decrease in antioxidants in heart, kidney, and liver tissues. CE treatment has been shown to attenuate cardiac damage by reducing serum troponin I (TpI) and creatine kinase-MB (CK-MB), renal damage by reducing creatinine and blood urea nitrogen (BUN), and liver damage by reducing alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Conclusion Co induced the production of oxidants and proinflammatory parameters and antioxidant depletion in heart, kidney, and liver tissues of rats. Our experimental results show that CE protects heart, kidney, and liver tissues against oxidative and inflammatory changes induced by CoCLl2.